An 8-mm port site hernia after robotic-assisted ileocecal resection: a case report - Changgi Ahn; Masatsune Shibutani; Kishu Kitayama; Hiroaki Kasashima; Yuichiro Miki; Mami Yoshii; Tatsunari Fukuoka; Tatsuro Tamura; Takahiro Toyokawa; Shigeru Lee; Kiyoshi Maeda (Surgical Case Reports)
Abstract Background Robotic-assisted surgery is steadily becoming more prominent. The majority of reports regarding port site hernias (PSHs) have involved laparoscopic procedures. Currently, it is common to suture the fascia at port sites that are 10 mm or larger; however, the closure of 5-mm port sites is not considered mandatory. The da Vinci® surgical system (Intuitive Surgical Inc., Sunnyvale, CA, USA) utilizes a distinctive 8-mm port. We report a case of an early-onset PSH at an 8-mm port site after robotic-assisted ileocecal resection. Case presentation A 74-year-old male patient with a body mass index of 19.7 kg/m2 was diagnosed with cecal cancer and underwent robotic-assisted ileocecal resection. A 3-cm midline incision was made at the umbilicus for insufflation. Under laparoscopic visualization, three ports (12 mm, 8 mm, and 8 mm) were inserted in the lower abdomen. An 8-mm port was inserted in the left subcostal region, and a 5-mm port was inserted in the left lateral abdomen. The procedure was performed without significant intraoperative complications. The fascia was closed only at the umbilicus and 12-mm port site; the fascia at the 8-mm port sites was not closed. The patient was initially discharged without complications; however, on postoperative day 11, the patient was urgently hospitalized again because of PSH incarceration. After manual reduction, the fascia was sutured closed under local anesthesia. The hernial defect was small and barely allowed the insertion of a little finger. There was no evidence of compression or significant damage to the fascia. On postoperative day 27, the patient was discharged after experiencing good recovery. Conclusions Robotic-assisted colectomy could contribute to the risk of PSHs because of its surgical characteristics. Although routine closure of the fascia at 8-mm port sites is not mandatory, it may be beneficial in certain cases.